Haiti: Between Emergency and Reconstruction - Jean-Marc Biquet (Revue Internationale de Politique de Développement)
Editor’s notes : This paper is a contribution to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy makers and practioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and policy makers.Authored by Jean-Marc Biquet, Research Officer at Doctors without Borders (MSF), the paper focuses on the failure of the aid system in Haiti. The country has been struck by two disasters in a raw: the January 2010 earthquake and a cholera epidemic starting in October the same year. Despite repeated requests to - and commitments from - the UN (UNOCHA in particular) to provide a response, we did unfortunately not get any written reaction to MSF's article. But we did receive critical comments by Andrea Binder, Associate Director of the Global Public Policy Institute (GPPi) in Berlin ‘Is the Humanitarian Failure in Haiti a System Failure?’, which we publish together with Mr Biquet's initial contribution. Dr. Biner has been involved in the Inter-Agency Real-Time Evaluation of the disaster response to the Haiti Earthquake.download the whole dabate in.pdf on http://poldev.revues.org/pdf/1600